2005
DOI: 10.1111/j.1365-2591.2005.00947.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of endodontic procedures on enterococci, enteric bacteria and yeasts in primary endodontic infections

Abstract: Enterococci, enteric bacteria and yeasts were present in primary endodontic infections. Enterococci, particularly Enterococcus faecalis and E. faecium were resistant to removal by root canal preparation followed by intracanal dressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
2
26

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 37 publications
5
55
2
26
Order By: Relevance
“…Recently, E. faecium has become one of the most important microorganisms in nosocomial and systemic infections [2][3][4][5], but few studies have reported the presence of E. faecium associated with endodontic infections [35,37,38]. In this study, E. faecium was found in only two patients (5.2%).…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Recently, E. faecium has become one of the most important microorganisms in nosocomial and systemic infections [2][3][4][5], but few studies have reported the presence of E. faecium associated with endodontic infections [35,37,38]. In this study, E. faecium was found in only two patients (5.2%).…”
Section: Discussioncontrasting
confidence: 45%
“…In this study, E. faecium was found in only two patients (5.2%). Ferrari et al [37] also reported a low prevalence of E. faecium in primary infections using culture and biochemical testing identification methods. However, some studies verified a high prevalence of E. faecium in persistent endodontic infections through identification using molecular methods (DNA-DNA hybridization checkerboard) [35,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that chemical-surgical preparation is able to achieve high levels of disinfection, but is unable to completely reduce the microbiota of the root canal system [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Os bacilos entéricos não excedem mais que 5% da microbiota dos canais radiculares infectados, mas a sua permanência no sistema de canais pode resultar em persistência da lesão periapical (Ferrari et al 2005). …”
Section: Querido (2006) Verificou a Presença De Enterobactérias Eunclassified